Home oxygen therapy for Thai preterm infants with bronchopulmonary dysplasia. What are the predictive factors for successful weaning: a 20-year review - Vipada Grajangdara; Anchalee Limrungsikul; Allan L. Coates; Harutai Kamalaporn (BMC Pediatrics)
Abstract Background Consequences of lung injury and inflammation in preterm infants with bronchopulmonary dysplasia (BPD) contribute to prolonged oxygen requirements. Home oxygen therapy (HOT) is an alternative way of respiratory support in infant with BPD. However, there is no consensus on weaning guidelines. Our objective is to identify the median age of HOT discontinuation and the factors that might predict the duration of HOT in a resource poor country. Methods All preterm (≤ 36 weeks’ gestation) infants diagnosed with BPD who required HOT after discharged from Ramathibodi Hospital during January 2000 – December 2019 comprised this retrospective study. Timing of HOT withdrawal was identified. Demographic data, severity of BPD, maternal condition, respiratory support, comorbidities, complications, and growth were recorded and analyzed as factors associated of home oxygen withdrawal. Results Of 8581 preterm infants born during the 20-year period, 563 (6.6%) had BPD. Among 40 infants treated with HOT, 18 (45%) were successfully weaned from oxygen within 12 months. The median corrected age (CA) of oxygen withdrawal was 13.8 months (8.5, 22.1). Longer duration of total respiratory support, longer length of hospital stay and poor growth determined by weight, length and head circumference were associated with longer duration of HOT. Greater weight gain was associated with a shorter duration of HOT at 12 months CA (adjusted OR, 1.97; 95% CI, 1.13–3.23; p = 0.015). Conclusions The median corrected age of oxygen withdrawal in Thai BPD infants was 13.8 months. Severe BPD and poor linear growth were associated with prolonged HOT.